ANALYSIS OF ANEMIA IN PREGNANT WOMEN - Apriani, Dina; Akhmad Dwi Priyatno; Ali Harokan (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Anemia is a health problem that can be experienced by toddlers, teenagers, pregnant women and even the elderly. The results of Riskesdas in 2018, it was recorded that 26.8% of children aged 5-14 years suffered from anemia and 32% of those aged 15-24 years suffered from anemia. meaning 3 out of 10 people suffer from anemia. This study aims to determine the factors associated with the incidence of anemia in pregnant women at the Tanjung Raja Community Health Center in 2024. The design of this research is quantitative with a cross-sectional approach. The population of this study was all pregnant women who visited the Tanjung Raja Community Health Center in 2024. The sample in this study was 86 people. The sampling method uses purposive sampling. This research was carried out on February 29 - March 31 2024. Data was collected using a questionnaire. Bivariate data analysis used the Chi-Square test and multivariate logistic regression. The research results showed a relationship between parity (p value 0.016) and side effects (p value 0.00) with the incidence of anemia in pregnant women at the Tanjung Raja Community Health Center, Ogan Ilir Regency in 2024. The most dominant factor in the incidence of anemia in pregnant women, namely side effects ( p value 0.00) (OR 181.2). The conclusion is that there is a relationship between parity and side effects with the incidence of anemia in pregnant women at the Tanjung Raja Community Health Center, Ogan Ilir Regency in 2024. The most dominant factor is side effects. For community health centers, community health centers should provide education on how to reduce the side effects of consuming fe tablets, both at the community health center and at the Posyandu.